M23 Follow-up in surgically treated lung cancer: CT scans versus chest radiographs. (December 2018) - Rowan, C; Lee Evans, H; McCarthy-Bell, K; Blaxill, P; Ameri, A
Abstract : Introduction: The optimum follow-up of patients who have undergone surgical resection of lung cancer is yet to be agreed. Within the local NHS trust, the standard post-operative follow-up in the first two years changed from chest radiographs (CXR) to CT scans in 2012. The aim of this study was to assess whether CT follow-up resulted in earlier identification of recurrence, increased radical treatment and whether there was a survival benefit. Method: A retrospective review was conducted of all patients who had undergone radical surgical management of lung cancer between January 2010 and December 2013. Chest radiographs every 4–6 months for a period of five years was the standard follow-up in 2010–2011 (CXR group), whilst the addition of CT scans at 3, 12 and 24 months were implemented in 2012–2013 (CT group). Recurrence and survival of the two groups were directly compared. Results: 110 patients were followed up post-operatively in the CXR group (wedge/segmentectomy 19 (17%), lobectomy 81 (74%) and pneumonectomy 10 (9%)), whilst 129 patients were in the CT group (wedge/segmentectomy 11 (9%), lobectomy 102 (79%) and pneumonectomy 16 (12%)). Histology consisted of 46 (42%) adenocarcinoma and 35 (32%) squamous cell carcinoma in the CXR group and 60 (47%) adenocarcinoma and 49 (39%) squamous in the CT group. Within five years of follow-up, 39 (35%) patients in the CXR group and 43 (33%) in the CT group were diagnosed with lung cancer recurrence or a new lung primary (recurrence 77% and new primary 23% for both groups). Of these, 25 (64%) patients of the CXR group and 33 (77%) of the CT group were diagnosed within the first two years. Lung malignancy was identified on routine follow-up imaging in 17 (44%) patients in the CXR group and 30 (70%) in the CT group. Radical treatment was received in 8 (21%) patients in the CXR and 20 (47%) in the CT group. Survival of the two groups is shown in figure 1. Conclusion: The results suggest that CT follow-up identifies recurrences earlier and results in more radical treatment. However, there is no significant survival benefit between the two groups.